Electronic circuits with MATLAB®, PSpice®, and Smith Chart - Yang, Wŏn-yŏng, 1953- (John Wiley & Sons, Inc., 2020)
"This book provides a student, researcher, or practicing engineer with the necessary design and modelling tools for validating electronic design concepts involving bipolar junction transistors (BJTs), field-effect transistors (FET), OP Amp circuits, and analog filters. Analytical solutions are presented with the results of MATLAB analysis (close to the theory) and PSpice simulation (close to the experiment) in the form of trinity. This approach gives the reader information about the state of the art and confidence in the legitimacy of the solution as long as the solutions obtained by using the two software tools agree with each other. For representative examples of impedance matching and filter design, the solution using MATLAB using Smith chart (Smith V4.1) arepresented for comparison and crosscheck. This approach is expected to give the reader confidence in and a deeper understanding of the solution"--